High Tibial Osteotomy for Genu Varum in Adults: Do Proprietary Implants Limit the Quality of Correction? - Solomin, LN (Strategies Trauma Limb Reconstr, 2020)
The surgical technique of proximal tibial osteotomy for genu varum in adults has evolved from a procedure using closing wedges of estimated sizes with staple fixation in the 1960s to using standard trauma internal fixation implants and, more recently, to gradual correction with software-guided hexapod external fixators. In the last two decades, implant manufacturers have also produced anatomical implants specific for such corrective osteotomies. This study evaluates the limits of using such proprietary implants for proximal tibial osteotomy in genu varum. MATERIALS AND METHODS: Scanograms (teleradiograms) of lower limbs of a patient were used to derive skiagrams (two-dimensional bony outlines of the extremities). From these, two-dimensional and three-dimensional models of varus deformities of the tibia with different values of mechanical medial proximal tibial angle (mMPTA, from 85° to 40°) were created. An analysis of the created deformity was carried out and a simulation for surgical correction was performed using an open wedge high tibial osteotomy with fixation using a proprietary (Tomofix, Synthes) implant. In addition, a 3D simulation technique was used to check the accuracy of the results obtained from the 2D simulation. RESULTS: In cases of mMPTA ≥80° with localisation of the apex of varus deformity at the level of the knee joint line, the standard technique used with the proprietary medial tibial plate produces good results. In cases of mMPTA ≤70°, fixation of the osteotomised fragments by the proprietary medial plate is poor owing to the anatomical contours of the implant. In these cases, a different type of osteosynthesis is needed. In cases of mMPTA ≤70°, the distance between the lower edge of the bone plate and the medial surface of the tibia after a proximal tibial osteotomy exceeds 11 mm and will result in unacceptable soft tissue tension around the implant. Mechanical axis deviation to the Fujisawa point produces mMPTA values outside the reference range of normal values. CONCLUSION: An osteotomy of the proximal tibia using a prescribed technique linked to a proprietary implant achieves good results only if performed within a certain range of deformity values. Pronounced varus deformities require a fundamentally different approach. This study reveals that surgeons undertaking corrective proximal tibial osteotomies for genu varum need to perform a comprehensive analysis of the deformity to allow for appropriate selection of patients. This will enable a consideration of the size and other characteristics of the deformity that will reduce the technical complications that may arise if the correction was performed using the recommended technique linked to a proprietary implant. HOW TO CITE THIS ARTICLE: Solomin LN, Chugaev DV, Filippova AV, et al. High Tibial Osteotomy for Genu Varum in Adults: Do Proprietary Implants Limit the Quality of Correction? Strategies Trauma Limb Reconstr 2020;15(1):13–22.